Bladder neck size and its association with urinary continence after robot‐assisted radical prostatectomy. Issue 2 (14th September 2022) - Kohjimoto, Yasuo; Higuchi, Masatoshi; Yamashita, Shimpei; Kikkawa, Kazuro; Hara, Isao
Abstract: Objectives: This study aims to determine whether bladder neck size (BNS) measured during surgery is associated with urinary continence after robot‐assisted radical prostatectomy. Patients and Methods: Between June 2015 and March 2019, 365 consecutive eligible patients undergoing robot‐assisted radical prostatectomy were enrolled into a prospective observational cohort study. The primary outcome was patient‐reported urinary continence status at 1, 3, 6, 12 and 24 months postoperatively, with continence defined as 0 pad/day. The primary exposure was BNS (largest diameter) measured intraoperatively just before performance of vesicourethral anastomosis. Other covariates included age, body mass index, NCCN risk category, nerve‐sparing, membranous urethral length measured intraoperatively and weight of the resected specimen. Results: Well‐preserved neurovascular bundle (bilateral/unilateral/none) was highly correlated with urinary continence status at every point after surgery. No difference could be seen between the group with BNS ≤17 mm and the >17‐mm group at 1, 3 and 6 months after surgery, but there was better urinary rate of continence in narrow BNS group (≤17 mm) at 12 and 24 months after surgery. Multivariate analysis showed both nerve sparing and bladder neck diameter to be independent factors affecting urinary continence at 12 and 24 months after surgery. Conclusion: Preservation of neurovascular bundles was associated with better urinary continence after surgery. Smaller BNS was associated with better urinary continence in late stages after surgery (12–24 months after surgery).